Mathematical Modeling of Biological Systems, Volume II Epidemiology, Evolution and Ecology,Immunology, Neural Systems and the Brain, and Innovative Mathematical Methods - Deutsch, Andreas; Parra, Rafael Bravo de la.; Boer, Rob J. de.; Diekmann, Odo.; Jagers, Peter; Kisdi, Eva.; Kretzschmar, Mirjam; Lansky, Petr.; Metz, Hans.; SpringerLink (Online service) (Boston, MA : Birkhäuser Boston, 2008)
This two-volume, interdisciplinary work is a unified presentation of a broad range of state-of-the-art topics in the rapidly growing field of mathematical modeling in the biological sciences. Highlighted throughout both works are mathematical and computational approaches to examine central problems in the life sciences, ranging from the organizational principles of individual cells to the dynamics of large populations. Volume I covers a number of areas, including: * Cellular Biophysics * Regulatory Networks * Developmental Biology * Biomedical Applications * Data Analysis and Model Validation Volume II examines a diverse range of subjects, including: * Epidemiology * Evolution and Ecology * Immunology * Neural Systems and the Brain * Innovative Mathematical Methods and Education Both volumes will be excellent reference texts for a broad audience of researchers, practitioners, and advanced students in this rapidly growing field at the intersection of applied mathematics, experimental biology and medicine, computational biology, biochemistry, computer science, and physics.
Epidemiology -- Could Low-Efficacy Malaria Vaccines Increase Secondary Infections in Endemic Areas? -- Modeling of the Invasion of a Fungal Disease over a Vineyard -- An Algorithm for Parameter Estimation in Nosocomial Infections -- Evolution and Ecology -- Evolutionarily Stable Investment in Anti-Predatory Defences and Aposematic Signalling -- The Tangled Nature Model of Evolutionary Ecology: An Overview -- Relative Advantage and Fundamental Theorems of Natural Selection -- Competitive Exclusion Between Year-Classes in a Semelparous Biennial Population -- On the Impact ofWinter Conditions on the Dynamics of an Isolated Population -- Planning for Biodiversity Conservation Using Stochastic Programming -- A Diffusion-Reaction Model of a Mixed-Culture Biofilm Arising in Food Safety Studies -- The Periodical Population Dynamics of Lottery Models Including the Effect of Undeveloped Seeds -- Immunology -- An Automata-Based Microscopic Model Inspired by Clonal Expansion -- Th1-Th2 Regulation and Allergy: Bifurcation Analysis of the Non-Autonomous System -- Architecture of Randomly Evolving Idiotypic Networks -- Analysis of Infectious Mortality by Means of the Individualized Risk Model -- Neural Systems and the Brain -- Neuromorphological Phenotyping in Transgenic Mice: A Multiscale Fractal Analysis -- A Quantitative Model of ATP-Mediated Calcium Wave Propagation in Astrocyte Networks -- Dynamics of Neural Fields with Distributed Transmission Speeds -- Estimation of Differential Entropy for Positive Random Variables and Its Application in Computational Neuroscience -- Dynamics of Integrate-and-Fire Models -- A Monte Carlo Method Used for the Identification of the Muscle Spindle -- Mechanisms of Coincidence Detection in the Auditory Brainstem: Examples -- Multi-Scale Analysis of Brain Surface Data -- The Spike Generation Processes: A Case for Low Level Computation -- Innovative Mathematical Methods and Education -- Offdiagonal Complexity: A Computationally Quick Network Complexity Measure-Application to Protein Networks and Cell Division -- An Analytically Solvable Asymptotic Model of Atrial Excitability -- A Bayesian Approach to the Quantitative Polymerase Chain Reaction -- A Model of Poplar (Populus sp.) Physiology and Morphology Based on Relational Growth Grammars -- Asymptotic Behavior of a Two-Dimensional Keller-Segel Model with and without Density Control -- Saturation Effects in Population Dynamics: Use Branching Processes or Dynamical Systems? -- Modelling and Simulation by Stochastic Interacting Particle Systems -- Teaching Mathematical Biology in a Summer School for Undergraduates.
Keywords: MATHEMATICS; IMMUNOLOGY; EPIDEMIOLOGY; BIOINFORMATICS; BIOLOGY -- MATHEMATICS; MATHEMATICS; MATHEMATICAL BIOLOGY IN GENERAL; MATHEMATICAL MODELING AND INDUSTRIAL MATHEMATICS; COMPUTATIONAL BIOLOGY/BIOINFORMATICS.; IMMUNOLOGY; EPIDEMIOLOGY; APPLICATIONS OF MATHEMATICS